Development and psychometric properties of an instrument to measure perception of aphrodisiac use among undergraduates in a southwestern Nigerian university - Olawumi Cecilia Fatade; Gabriel Ifeoluwa Makinde; Ayodeji Matthew Adebayo (BMC, 2024)
Abstract A tool to measure perception of aphrodisiac use by undergraduates students of University of Ibadan, Oyo State, Nigeria was developed and validated. The study was hinged on several theories that could explain potential to use aphrodisiac among the youths. An exploratory mixed methods design was used to develop a scale to measure perception of aphrodisiac use by undergraduate students of University of Ibadan. Qualitative data collection was performed among thirty equally represented male and female students and five key informant interview participants while 919 participants completed the quantitative phase (surveys). Integration of matched qualitative themes from FGD/KII to survey domains was achieved through the 'building approach'. Qualitative themes assessing perceptions of aphrodisiac use by university undergraduate students were used to develop original survey items as well as new survey items peculiar to research subjects. Exploratory factor analysis was deployed on polychoric correlation matrix of the items using R-statistical packages. Further model fit analysis was conducted using confirmatory factor analysis on the items suggested by EFA as well as composite reliability and construct validity tests for the constructs. Mean Z-scores of factors were computed against socio-demographics and symptoms of aphrodisiac use among respondents that have ever used it. Most respondents (84.3%) were under 25 years, mostly male (58.4%) and singles (96.3%), with 41.3% earning ≤20,000 naira monthly. The enhanced content validity of the items from mixed method analysis yielded two major domains. Two succession of factor analyses and a structural equation modeling suggested that a first-order model is good fit for experimental data (TLI = 0.931; CFI = 0.948; SRMR = 0.047; RMSEA = 0.083). The four-factor solution to the model included: prolonged sexual performance, use without erectile dysfunction or medical advice, treatment of erectile dysfunction and recreational purposes with an internal and composite reliability that ranged from 0.62-0.92 and 0.63-0.92. The validation with socio-demographics and consequences of aphrodisiac use indicated that: Male respondents, those older than 20years, the married, those from poorly educated parent and sufferers of all related consequences had statistically significant differences with poor perception of aphrodisiac use' domains. This validated instrument is good for assessment of perception of aphrodisiac use among students in tertiary institution albeit with caution. A version of the scale that is broadened with highly refined items and tested for high internal validity is suggested.